(untitled) (Parliamentary Studies, 2015)
The article discusses the characteristic of the first failed referendum of the 20th century, which testified to complicated relations between the executive power and society inrespect of the above-mentioned campaign. The 1922 Constitution of Lithuania provided for the possibility of holding a referendum. However, this possibility was unlikely to be made use of in the immediate future. Nonetheless, in the new political realities that formed after 17 December 1926, the idea of the referendum “was pulled out of the drawer” seeking to implement the possible reform of the Constitution. The idea of the referendum acquired different shapes of value in the vision of the prevailing political forces. The analysis of the correspondence between the county governor sand the Ministry of the Interior on the issues of the referendum revealed different opinions and reactions of society with respect to the campaign being organized. The study of the public mood testified to the significance of certain external influences (political parties, the clergy), certain precedents of collective-political awareness that have formed (right is mand leftism of individual public groups), the feeling of insecurity, indecisiveness which was sometimes permeated with both the signofphobia and that of absenteeism. The forecast of the irassessment sentanin secure signal to the initiators of the referendumas to the expected favourable voting results. Possibly unfavourableselfdetermination of society could have become one of the reasons that determined the withdrawal of the ruling forces from the irintention to conduct the referendum. As the ruling majority feared to make a misstep, mostlikely it was decided to prevent the society itself from “erring” either. It is supposed that, alongside other possible hindrances, preliminary self-determination of the society could have become a constituent part of the “failure” of the referendum.